Inflammatory potential of diet and mortality in Australian adults - Azam Majidi; Maria Celia B Hughes; Imogen K Webb; Kyoko Miura; Jolieke C van der Pols (Cambridge University Press, 2024)
Abstract Objective: Inflammation is implicated in chronic diseases including cancer and CVD, which are major causes of mortality. Diet can influence inflammation status. We therefore examined whether the inflammatory potential of a person's diet is associated with mortality. Design: The inflammatory potential of the usual diet was assessed by calculating Dietary Inflammatory Index (DII) scores from repeated FFQ data (collected in 1992, 1994 and 1996), placing each participant's diet on a continuum from anti- to pro-inflammatory. DII scores were analysed as a continuous variable and as categories by creating quartile groups. Death registry data were used to ascertain all-cause mortality and separately mortality from CVD, cancers and other causes between 1992 and 2022. Cox proportional hazard regression analysis was used to calculate adjusted hazard ratios (HR) with 95 % CI, comparing higher and lowest quartile groups, or HR change per one DII unit increase. Setting: Nambour, Australia. Participants: A community-based sample of 1440 adults aged 25-75 years. Results: During follow-up, 488 participants died, including 188 from CVD, 151 from cancer and 170 from other causes. Participants in the most pro-inflammatory diet group were at increased risk of all-cause mortality (HRQ4 v. Q1 = 1·55; 95 % CI 1·19, 2·03; P < 0·001) and other-cause mortality (HRQ4 v. Q1 = 1·69; 95 % CI 1·12, 2·54; P 0·01). A one-unit increase in DII score was associated with a 36 % increased risk of CVD among those younger than 55 years of age (HR for a one-unit increase in DII score 1·36, 95 % CI 1·04, 1·78). The risk of cancer mortality was also increased for those with a more pro-inflammatory diet in age ≤ 55 years (HR for a one-unit increase in DII score 1·20, 95 % CI 1·02, 1·40) and age 56-65 years (HR for a one-unit increase in DII score 1·11, 95 % CI 1·00, 1·23). Conclusions: A pro-inflammatory diet increases the risk of all-cause mortality. Our results support the promotion of anti-inflammatory diets to help promote longevity.